Carbon dots for all-in-one detection and degradation: The role of photoinduced electron transfer. Issue 6 (December 2022) - Huang, Jiaoyan; Long, Caicheng; Zhang, Lei; Qing, Taiping; Zhang, Peng; Qing, Zhihe; Feng, Bo
Abstract: Using organic pollutants as natural electron transfer mediators and carbon dots (CDs) as photosensitizers for integrated monitoring and purification of contaminants is a new game-changing idea. We herein first reported a novel dual-functional platform of detection and degradation based on the photoinduced electron transfer (PET) process between tetracycline (TC) and CDs. On the one hand, CDs can be used as fluorescence probes for TC detection with good sensitivity and selectivity. On the other hand, they display an excellent photodegradation ability for TC without any external photosensitizer or cocatalyst. Studies suggested that the PET process is beneficial for the transfer of electrons from TC to CDs, which further accelerates electron transfer and suppresses the recombination of electron-hole pairs, thereby improving the fluorescence quenching efficiency and photocatalytic activity. We believe this study can offer referable directions and theoretical guidance for the development of effective environmental pollution control and remediation technologies using CDs. Graphical Abstract: In this work, we reported an approach for all-in-one detection and degradation of pollutants in water environment based on a photoinduced electron transfer (PET) process between tetracycline (TC) and carbon dots (CDs). PET process is beneficial for the transfer of an electron from TC to CDs, which efficiently accelerates electron transfer and inhibits the recombination process of electron-hole pairs, thereby improving the fluorescence quenching rate and photocatalytic activity. We believe that this study can offer referable directions and theoretical guidance for the development of effective environmental pollution control and remediation technologies using CDs. ga1 Highlights: The as-synthesized CDs have good fluorescence characteristics and redox capacity. CDs can be a multifunctional platform for all-in-one detection and degradation. The photoinduced electron transfer from TC to CDs leads to fluorescence quenching. The PET process promotes direct photolysis and sensitized photodegradation of TC.